2018
DOI: 10.1111/ppc.12312
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure and psychometric properties of an Arabic‐translated version of the Body Appreciation Scale‐2

Abstract: A psychometrically sound BAS-2 may now facilitate the conduct of cross-cultural work that includes the Arabic-speaking population, an often-neglected ethnic group in most body image studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…The BAS has been shown to have good discriminant, construct, and incremental validities. Among Arabs countries, the BAS has been shown to have good discriminant, constructive, and incremental validities [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BAS has been shown to have good discriminant, construct, and incremental validities. Among Arabs countries, the BAS has been shown to have good discriminant, constructive, and incremental validities [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The higher the overall score the higher body appreciation is. The validity of this tool has been approved for Arabic culture respondents (Vally et al, 2018). In this study, Cronbach's alpha of this test was .934 showing high reliability.…”
Section: Study Instrumentsmentioning
confidence: 73%
“…Items are rated on a five‐point scale, ranging from 1 ( Never ) to 5 ( Always ), and the mean composite score was computed by averaging the ratings of the 10 items, with higher scores being reflective of greater body appreciation . The BAS‐2 has been shown to be psychometrically sound in samples from a range of diverse sociocultural contexts, including the UAE . The internal consistency of the BAS‐2 in the present sample was excellent ( α = .91).…”
Section: Methodsmentioning
confidence: 79%
“…Given that body appreciation has been shown to be associated with several favorable mental health outcomes, any behaviors that serve to promote the cultivation of elevated levels of the construct should be considered preferable. This study revealed that body appreciation may be related to interest in the use of cosmetic enhancing procedures, indirectly, as these behaviors allow the individual to highlight and express aspects of themselves that they view to be unique.…”
Section: Discussionmentioning
confidence: 99%